STYLISTIC STYLES ANALYSIS ON COVID-19 BROADCAST OF CNN INDONESIA.COM NEWS - Qori’ah Qori’ah (EL2J (English Language and Literature Journal), 2022)
This writer discussed Covid-19 broadcast. The aims of this writer helped societies and increase understanding of lexicons in Covid-19 broadcast. The writer took the data from January 16th till 26th 2021 that is presented by a journalist in CNN Indonesia.com news. This writer took the data from the video and took the script. There were nineteen data to analyze to be lexicons in Covid19. The writer used qualitative descriptive method to explain the existence of a phenomenon that occurs in societies. The writer took qualitative descriptive research using stylistic style analysis because the writer described lexicons in Covid-19 broadcast. This writer analyzed stylistic style of microstructure of discourse proposed by Van Dijk. The stylistic styles data was used when the journalist conveyed lexicons in Covid-19 broadcast. The lexicons on the text gave the explanation of what was a response the societies after they had known about lexicons in Covid-19. The result of this research was to find out lexicons in Covid-19 broadcast. Thus, increasing insight is for the societies. The writer concluded that lexicons in Covid-19 were very beneficial for the societies to avoid or prevent Covid-19.